Предмет: Математика,
автор: kate15021
(4+9b)²+(9b+2)(2-9b)=0
Ответы
Автор ответа:
9
Ответ:
(4+9b)²+(9b+2)(2-9b)=0
4^2+2*4*9b+(9b)^2+18b-81b^2+4-18b=0
16+72b+81b^2+18b-81b^2+4-18b=0
с противоположными знаками числа сокращаем
остается
20+72b=0
72b=-20
b=-20/72
b=-0.16666
Пошаговое объяснение:
Похожие вопросы
Предмет: Химия,
автор: chornobei2005
Предмет: Русский язык,
автор: rakymzhanserikov
Предмет: Українська мова,
автор: darjavasechko
Предмет: География,
автор: ira918700
Предмет: Математика,
автор: spro5678